PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI SMP NEGERI 8 KOTA PROBOLINGGO - jurnalmap map; Nur Sulastri; C. Sri Hartati; Soenarmi ÔÇÄ (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
The purpose of this study was to determine: 1. Partially work motivation and work environment on the performance of teachers of SMP Negeri 8 Probolinggo City. 2. To find out the simultaneous influence of work motivation and work environment on the performance of teachers of SMP Negeri 8 Probolinggo City. This study uses a descriptive analysis method with a quantitative approach, data collection techniques using a questionnaire distributed throughout the population. Analysis of the data used in this study are: multiple linear regression analysis, t test (partial) and F test (simultaneous). Conclusion Based on data analysis: it is explained that: 1. Work motivation and work environment have a partial effect on the performance of teachers of SMP Negeri 8 Probolinggo City, proven by t-test (partially) 2. Based on the results of the calculated F value (simultaneously) work motivation and the work environment has a positive and significant effect on the performance of Probolinggo City 8 Junior High School teachers. Based on the t test results it is known that the work environment has a dominant influence on the performance of teachers of SMP Negeri 8 Probolinggo City. Keywords: work motivation, work environment and performance